2010
DOI: 10.1063/1.3462985
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of multilayer Laue lenses by a combination of pulsed laser deposition and focused ion beam

Abstract: X-ray diffractive techniques using Fresnel zone plate lenses of various forms are of great technical interest because of their ability to form images at very high spatial resolution, but the zone plates are unfortunately very hard to produce by lithography. Alternatively, multilayer Laue lenses (MLLs) and multilayer zone plates are used due to the higher and easily adjustable aspect ratio necessary for different wavelengths. In this paper, the fabrication of a MLL by a combination of pulsed laser deposition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 21 publications
0
10
0
3
Order By: Relevance
“…The vertical anisotropy is increased by high fluorine content within the plasma. Higher etching rates are achieved with SF 6 , as compared to CF 4 . The use of ICP combined with RIE provides higher ion energy, and thus both a higher etching rate and deeper anisotropic etching is obtained.…”
Section: Resultsmentioning
confidence: 80%
“…The vertical anisotropy is increased by high fluorine content within the plasma. Higher etching rates are achieved with SF 6 , as compared to CF 4 . The use of ICP combined with RIE provides higher ion energy, and thus both a higher etching rate and deeper anisotropic etching is obtained.…”
Section: Resultsmentioning
confidence: 80%
“…Details of the complex deposition and assembling processes are described in [9,10]. The design parameters for plane wave illumination are summarized in Table 1.…”
Section: Fabrication Of the Multilayer Laue Lensmentioning
confidence: 99%
“…However, as to our knowledge, they have not yet been applied as diffractive optics in the soft X-ray regime so far. Krebs et al have recently shown that MLLs can be effectively manufactured by pulsed laser deposition (PLD) and focused ion beam (FIB) techniques [9,10]. These novel structures show nearly no cumulative roughness and no damage from rough dicing or polishing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Fresnel zone plates (FZP) represent the state of the art X-ray lenses, whereas multilayer Laue lenses (MLL) are an emerging approach for new X-ray optics [2]. Recent studies at synchrotron radiation facilities solely investigated the focusing properties of MLLs [3][4][5]. Their imaging capabilities were not exploited so far experimentally to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Approaches like zone plate stacking push the limits only slightly further [11,12]. As a major advantage, MLL optics do not have any upper bounded aspect ratio limitation since they are cut out of a multilayer stack, manufactured by thin film deposition [4]. The thicknesses of those layers follow the zone plate law, and layer thicknesses down to 1 nm can be produced with high quality [13].…”
Section: Introductionmentioning
confidence: 99%